1975
DOI: 10.1542/peds.56.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Osteomalacia Associated With Anticonvulsant Drug Therapy in Mentally Retarded Children

Abstract: A survey of 289 severely retarded inpatients at a school for retarded children in American Fork, Utah revealed 67 patients with osteomalacia as defined by hypocalcemia, hypophosphatemia, elevated serum alkaline phosphatase levels, and appropriate bone changes. Investigation of the variables which might influence bone mineralization revealed no differences in age, sex, physical activity, sunshine exposure, or dietary intake of vitamin D between the osteomalacia and nonosteomalacia groups. However, all of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Weight Z‐score is the best correlate of bone mineral density Z‐score in these children (57). Limited ambulation, increased duration of anticonvulsant therapy, and reduced sun exposure contribute to the pathogenesis of osteopenia (56‐61). Dietary calcium, vitamin D, and phosphorus intakes are below the DRI in 50% to 80% of these children (31,60,61).…”
Section: Osteopeniamentioning
confidence: 99%
“…Weight Z‐score is the best correlate of bone mineral density Z‐score in these children (57). Limited ambulation, increased duration of anticonvulsant therapy, and reduced sun exposure contribute to the pathogenesis of osteopenia (56‐61). Dietary calcium, vitamin D, and phosphorus intakes are below the DRI in 50% to 80% of these children (31,60,61).…”
Section: Osteopeniamentioning
confidence: 99%
“…Craniofacial contribution of fibrous dysplasia is frequent, with 10% to 27% of monostotic patients and up to 50% of polyostotic patients having an association with one or more craniofacial bones. Fibrous dysplasia is initiated mainly by a mutation in GNAS 1 α [ 7 , 8 ]. The lesions' radiographic unique features depend on the condition's phase.…”
Section: Introductionmentioning
confidence: 99%
“…Early reports suggested that 12% to 65% of epileptic patients have abnormal bone mineral density (Hahn et al 1972, Mosekilde et al 1977, Petty et al 2005, Stephen et al 1999). Enzyme inducers and non‐enzyme inducers cause abnormalities in calcium metabolism, including hypocalcemia, hypophosphatemia, elevated serum alkaline phosphatase, serum parathyroid hormone and low vitamin D (Pack et al 2003, Andress et al 2002, Boluk et al 2004, Christiansen et al 1973, Richens and Rower 1970, Tolman et al 1975, Berr et al 1983, Marshall et al 1996, Farhat et al 2002). The consequences of fractures include hospitalization, loss of independence and death.…”
mentioning
confidence: 99%